The Teachers’ Technique in Teaching Speaking Skill - St ainun pratiwi Nasaruddin; Bahtiar (Inspiring: English Education Journal, 2021)
The purpose of the research was to analyze the teachers' technique in teaching speaking Englishand to find out the students' speaking skill at Second Grade of Smk Negeri 3 Parepare. Theresult of the study is beneficial for teachers and students because they will get properinformation about teachers' technique in teaching speaking English and it can be a reference tofind out a suitable method in another teaching process. Two English teachers and 58 studentswere the first and second samples of the study. The researcher method was Mix Method, itanswers the question in this research with qualitative and quantitative. Interviews anddocuments were used to collect the data. Analyzing the data, the researcher found that theteachers’ techniques in teaching speaking skill at Second Grade of Smk Negeri 3 Parepare wereretelling and discussion, it clearly found as effective techniques which could develop thestudents' speaking skill.